Strengthening adverse drug reaction reporting in Nepal - Jha, Nisha; Rathore, Devendra Singh; Shankar, Pathiyil Ravi; Gyawali, Sudesh; Hassali, Mohamed Azmi; Alshakka, Mohammed; Alshammri, Thamir M. (Asian Journal of Medical Sciences, 2015)
Pharmacovigilance in Nepal is still in infancy. Till date only healthcare professionals are involved and the problem of underreporting is seen. The national pharmacovigilance centre is located in the national regulatory authority of Nepal, i.e. Department of Drug Administration (DDA). Lack of adequate human resources for managing the pharmacovigilance program in Nepal has been a limitation for the growth of pharmacovigilance activities. Currently, there is neither any involvement of community pharmacists in Adverse Drug Reaction (ADR) reporting process nor any involvement of consumers for the same. This paper reviews the current status of pharmacovigilance and mentions possible benefits of involving consumers or patients in the existing pharmacovigilance program. A systematic review were conducted by searching different databases like PubMed, Google scholar, EMBASE, NepJOL, and Scopus. This study also describes the role of healthcare professionals in ADR reporting, possible reasons for underreporting of ADRs, regulatory perspectives and benefits of involving consumers in pharmacovigilance. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11659 Asian Journal of Medical Sciences Vol.6(4) 2015 9-13